The discursive representation of the use of English on facebook / Lionel Keith Vytialingam - Lionel Keith , Vytialingam (2019)
The present case study investigates discursive strategies incorporated by tertiary student members of a social networking (Facebook) group in their representations of themselves and others in terms of English language proficiency. Borrowing analytical tools from Wodak’s (2001), and Reisigl and Wodak’s (2009) Discourse Historical Approach, data comprising online wall postings on the Facebook Group page and interview responses of eight selected participants are analysed for discursive strategies of self and other representation. Additionally, investigation is made into argumentation strategies utilised to legitimise these representations. Analysis has yielded findings that indicate that members who self-identify as less proficient English users, as well as those who self-identify as more proficient English users, utilise referential and predicational strategies to discursively represent themselves positively and the other negatively surrounding the topics of their sense of solidarity as students, the perceived economic future, and the reputation of Malaysia as an English-speaking nation. Findings also reveal that in relation to the discourse topic of education and employment that tie in closely with ideologies disseminated by media reports and opinion leaders, members who self-identify as less English proficient utilise referential and predicational strategies to represent themselves negatively as problematic and facing economic difficulties, while representing the other positively as more deserving of employment and primed for a better economic future. Argumentation analysis reveals that members evoke various topoi in their justification of the representations of themselves and others. Findings are reported and explained in detail in this dissertation.